Scientific signals in Surat Al-Nahal Study in the scientific explanation - نظام الدين نجم الدين نور (Al-Adab Journal, 2018)
Al-Nahal focused on major topics Creed: divinity, revelation, and rebirth. The other side has befallen the purposes related to those key topics. It is the most important facts highlighted by the fact Sura big oneness, that link between the religion of Abraham and the religion of Muhammad, peace be upon him . It also highlighted the fact that the divine will and human will, with respect to faith and disbelief and guidance and misguidance. And it showed the function of the apostles, and the year of the rejecters of God in them. The theme of the analysis and the prohibition of idolatry and illusions . I talked about immigration for the sake of God, and the temptation of Muslims in their religion, and disbelief after faith, and kicks this whole God. In addition to issues of belief, Sura has meant to the statement of the transaction themes: justice, benevolence, and spending, and the fulfillment of the Covenant, and other topics based on faith behavior. And named Surat Al-Nahal; because they talked about these beneficial insects, which provide food for humans beneficial panacea, which are among the blessings that God has bestowed on them slaves. Also called Al-Ni’am (graces); and then said God the blessings bestowed by God to worship, blessing the rain, and the grace of the sun, moon and stars, and the blessing of children and wife.